HEPCIDIN AND IRON HOMEOSTASIS - Ganz, Tomas (2012)
Despite fluctuations in dietary iron intake and intermittent losses through bleeding, the plasma iron concentrations in humans remain stable at 10–30 μM. While most of the iron entering blood plasma comes from recycling, appropriate amount of iron is absorbed from the diet to compensate for losses and maintain nontoxic amounts in stores. Plasma iron concentration and iron distribution are similarly regulated in laboratory rodents. The hepatic peptide hepcidin was identified as the systemic iron-regulatory hormone. In the efferent arc, hepcidin regulates intestinal iron absorption, plasma iron concentrations, and tissue iron distribution by inducing degradation of its receptor, the cellular iron exporter ferroportin. Ferroportin exports iron into plasma from absorptive enterocytes, from macrophages that recycle the iron of senescent erythrocytes, and from hepatocytes that store iron. In the more complex and less well understood afferent arc, hepatic hepcidin synthesis is transcriptionally regulated by extracellular and intracellular iron concentrations through a molecular complex of bone morphogenetic protein receptors and their iron-specific ligands, modulators and iron sensors. Through as yet undefined pathways, hepcidin is also homeostatically regulated by the iron requirements of erythroid precursors for hemoglobin synthesis. In accordance with the role of hepcidin-mediated iron redistribution in host defense, hepcidin production is regulated by inflammation as well. Increased hepcidin concentrations in plasma are pathogenic in iron-restrictive anemias including anemias associated with inflammation, chronic kidney disease and some cancers. Hepcidin deficiency causes iron overload in hereditary hemochromatosis and ineffective erythropoiesis. Hepcidin, ferroportin and their regulators represent potential targets for the diagnosis and treatment of iron disorders and anemias.